Reinforcing a metal-based composite with a percentage of MgO particale to improve some of its properties and its relationship to conventional heat treatment - Shaymaa M.F (Tikrit Journal of Pure Science, 2023)
This research involved the manufacture of three compounds using powdered metallurgy technology through the reinforcement of the AlNi with addition percentage (40%), (35%) and 30% (MgO) ceramic reinforce phase to compound of A , B and C respectively and thermally treated In the traditional way